2017
DOI: 10.1364/boe.8.001981
|View full text |Cite
|
Sign up to set email alerts
|

Subsampled phase retrieval for temporal resolution enhancement in lensless on-chip holographic video

Abstract: On-chip holographic video is a convenient way to monitor biological samples simultaneously at high spatial resolution and over a wide field-of-view. However, due to the limited readout rate of digital detector arrays, one often faces a tradeoff between the per-frame pixel count and frame rate of the captured video. In this report, we propose a subsampled phase retrieval (SPR) algorithm to overcome the spatial-temporal trade-off in holographic video. Compared to traditional phase retrieval approaches, our SPR a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…The corresponding constraints, i.e., amplitude in Fourier domain and support in object domain, are updated accordingly. Ryu et al [2] reported the issue of space-time resolution tradeoff and proposed a sub-sampled phase retrieval (SPR) scheme for temporal resolution enhancement. Here, we propose a dictionary-based method for further improving the reconstruction results.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The corresponding constraints, i.e., amplitude in Fourier domain and support in object domain, are updated accordingly. Ryu et al [2] reported the issue of space-time resolution tradeoff and proposed a sub-sampled phase retrieval (SPR) scheme for temporal resolution enhancement. Here, we propose a dictionary-based method for further improving the reconstruction results.…”
Section: Methodsmentioning
confidence: 99%
“…On-chip in-line holography (OIH) is a lens free imaging method that offers high resolution over a wide field-ofview [1,2]. However, high spatial resolution requires longer time for sampling and processing, yielding a low frame rate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second one focuses on lens-free on-chip imaging setup for in vivo scenes of biological samples. 42…”
Section: Introductionmentioning
confidence: 99%
“…[10][11] The resolution of an image is also restricted by sensor pixel sampling due to large pixel size. [12][13][14] In lensless microscopy, this factor is corrected through x − y translation of the illumination source. 8 The lensless microscopic system is made more compact through the side illumination technique 15 to reduce the complexity while achieving a large field of view.…”
mentioning
confidence: 99%